The Differences in Children Music Skills that Follow Kolintang Extracurriculars with Children who Do Not Follow Kolintang Extracurriculars - Harfiani, Mei; Nugroho, Agustinus Arum Eka (Jurusan PGPAUD FIP UNNES, 2020)
Children have many abilities that continue to develop; there are musical abilities of children who also develop. At the Kintelan Semarang State Kindergarten there is a kolintang extracurricular to support the development of children's musical abilities, but not all children join the kolintang extracurricular. The aim of this study was to determine the musical ability of children who take kolintang extracurricular activities with children who do not take kolintang extracurricular activities at Kintelan Semarang State Kindergarten. This research uses quantitative research with comparative methods. The subject and population of this study were children of Class B of Kintelan Semarang State Kindergarten. The data collection was carried out by distributing questionnaires. The data analysis technique used is the analysis of the independent sample t-test, which was previously subjected to a prerequisite test, namely the normality and homogeneity tests. The results showed that children who took kolintang extracurricular activities got a minimum value of 86, a maximum score of 134, and an average value of 119.79, while children who did not take extracurricular kolintang received a minimum value of 70, a maximum value of 114, and an average value of 90.93. tcount > ttabel is 4,389> 1,701 and Sig <0.05 is 0,000 <0.05. The conclusion of this study is that there is a significant difference in the musical abilities of children who take kolintang extracurricular activities with children who do not take kolintang extracurricular activities. The suggestion of this research is that the teacher should motivate all children to be able to participate in kolintang extracurricular activities so that their musical abilities can develop optimally.